2010
DOI: 10.1021/bm100476r
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering Using Electrospun PCL Nanofiber Meshes and MSCs

Abstract: Mesenchymal stem cells (MSCs) have been recognized for their ability to differentiate into cells of different tissues such as bone, cartilage, or adipose tissue, and therefore are of great interest for potential therapeutic strategies. Adherent, colony-forming, fibroblastic cells were isolated from human bone marrow aspirates, from patients undergoing knee arthroplasties, and the MSCs phenotype characterized by flow cytometry. Afterward, cells were seeded onto electrospun polycaprolactone nanofiber meshes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 45 publications
4
78
0
Order By: Relevance
“…By contrast, melt electrospinning generates a liquid polymer by heating the material until it liquifies [53]. Both electrospinning techniques have been successfully applied to the field of tissue engineering as way to produce a variety of tissue types [65][66][67][68].…”
Section: Fabrication Of Fibrous Scaffolds Using Solution and Melt Elementioning
confidence: 99%
“…By contrast, melt electrospinning generates a liquid polymer by heating the material until it liquifies [53]. Both electrospinning techniques have been successfully applied to the field of tissue engineering as way to produce a variety of tissue types [65][66][67][68].…”
Section: Fabrication Of Fibrous Scaffolds Using Solution and Melt Elementioning
confidence: 99%
“…Reprinted with permission from [15], Copyright could also be a reason for regeneration issues [12]. Da Silva et al [116] used PCL nanofiber meshes to culture mesenchymal stem cells in a multichamber flow perfusion bioreactor. They showed that there was an increased rate of differentiation of MSCs into chondroitic cells.…”
Section: Musculoskeletal Tissuementioning
confidence: 99%
“…Poly(ε-caprolactone) (PCL) is an FDA approved biodegradable polymer used for a wide range of biomaterial applications [24,27,[34][35][36]. Moreover, it is easily electrospun into nanofiber using a range of solvents and preparation parameters [34][35][36][37][38][39][40]. Electrospinning has a wide range of uses due to the customization available.…”
Section: Introductionmentioning
confidence: 99%